PENGEMBANGAN INSTRUMEN TES ESAI BERBASIS KEMAMPUAN BERPIKIR KRITIS PADA MATERI GARIS DAN SUDUT DI TINGKAT SMP - Kusumo, Bangun Jati; Hepsi Nindiasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Research and development (R&D) is the focus of this study. The purpose of this research is to develop an essay exam instrument for junior high school students based on critical thinking abilities about lines and angles. In this study, "critical thinking skills" refers to Robert Ennis's indicators. The Wilson model as well as the Oriondo and Antonio models are the research models that are employed. The first step in the research process is to identify curriculum-specific learning objectives and choose the content that will be created into an essay test. Expert validation of the product comes next, after which the required changes are made. Validation, reliability, level of difficulty, and distinguishing power tests are performed once the questions have been revised in order to provide a genuine essay exam product. Twenty students from SMPN 2 Rangkasbitung in grade VII were randomly selected to take the test. Five good essay-format questions focused on critical thinking abilities regarding lines and angles are the outcome of this study.